Engineering materials 2 an introduction to microstructures and processing - Ashby, M. F. (Butterworth-Heinemann, 2012)
Engineering Materials 2 is a best-selling stand-alone text in its own right for more advanced students of materials science and mechanical engineering, and is the follow-up to its renowned companion text, Engineering Materials 1: An Introduction to Properties, Applications & Design . This book develops a detailed understanding of the fundamental properties of engineering materials, how they are controlled by processing, formed, joined and finished, and how all of these factors influence the selection and design of materials in real-world engineering applications. One of the best-selling materials properties texts; well known, well established and well liked Each chapter is designed to cover the content of one 50-minute lecture - Makes it easy for instructors to plan a syllabus around the text Enhanced pedagogy including many more case studies, worked examples, homework problems and updated illustrations - Makes learning the material easier Includes numerous detailed case studies throughout - allows students to see the practical applications of the material just presented in their lecture Online support materials include a set of interactive materials science tutorials - allowing students to test their knowledge of materials science in a fun, interactive way.
Keywords: Materials.; elektronické knihy; electronic books